The Design of Work Facility and Description of Job Characteristic to Improve Employee Performance at PT. Ferlina Jaya Mandiri Gorontalo - Melan Angriani Asnawi (International Journal of Applied Business and International Management, 2018)
The research aimed to know to what extent the effect of work facility and job characteristic both partially and simultaneously on employee performance. It involved 30 employees as population while its samples were determined by using random sampling. Research method applied a quantitative method by using multiple linear regression analysis. The finding of research found that partially, work facility variable had a positive effect on employee performance with value of ttable for 7,220 which was higher than the value of t count for 1,703 and at significance value of 0,000. Meanwhile, partially, job characteristic variable did not have a significant effect on employee performance, where the value of t count was 1,363 that was lower than the value of t table for 1,703, and the significance value was 0,184. Research finding (R2) was 0,793, and it showed that the effect of variable X1 and X2 was 79,3% had a positive effect on variable Y.